Effects of Nb-doping on the micro-structure and dielectric properties of (Bi0.5Na0.5)TiO3ceramics - Napatporn Petnoi (2018)
Bismuth sodium titanate [(Bi 0.5 Na 0.5 )TiO 3 or BNT] ceramics incorporated with 0, 1, 5, 10, 15 and 20 mol% niobium were prepared by conventional solid state reaction method. The green bodies were sintered at 1050 °C for 2 h to obtain dense ceramics. The effects of substitution of niobium ion for titanium ion in BNT ceramics on micro-structure and dielectric properties were investigated. X-ray diffraction analysis showed the presence of a secondary phase when more than 5 mol% niobium was added. Within the solubility limit, Nb doping caused the grain size of BNTNb to be smaller than the undoped sample. The investigation of the dielectric properties showed that the transition temperature (T c ) was found to shift towards lower temperature as the content of Nb increased. In this research, the donor-type behavior and induced charged defects had significant influence on the electrical properties of Nb-doped BNT ceramics. © 2012 Elsevier Ltd and Techna Group S.r.l.